English grammar usage for technical students - Saahul, Mopidevi sanjay; Raju, G Victor Emmanuel; Reddy, G Shailaja (Delhi DPS Publishing House, 2022)
There are many books about grammar and other concepts of English in the market today. This book is a collection of all kind of topics that are prescribed for all the engineering students those are pursuing in all affiliated engineering colleges of JNTU, Hyderabad.
Keywords: English Grammar